(untitled) (Nordic Journal of African Studies, 2005)
Modals have been thought to be fairly homogeneous in terms of usage throughout the English-speaking world. However, corpus-based studies (e.g. Coates 1983; Katikar 1984; Krogvig & Johansson 1991; Collins 1988) have established that these verbs indeed vary according to region and to a certain extent register. This study examines the degree of such variation in Cameroon English by comparing frequency occurrences of must and should in the Cameroon English database with findings of similar corpus-based investigation in British English as reported in Coates (1983) and Johns (1991). Findings reveal notable semantic and stylistic variations in Cameroon English (compared with British English). For example, root meanings of these modals are very frequent and for the most part they are used in very ‘restrictive’ ways. Furthermore, certain elements of context that normally mark spoken informal English occur freely in Cameroon English ; making the distinction between formal and informal usage blurred.